Early Oral Feeding Following Intestinal Surgery is it Safe? - Muqdad Fuad Abd.Alkareem (Diyala Journal of Medicine, 2019)
Background: A period of starvation (“nil by mouth”) is common practice after gastrointestinal surgery during which an intestinal anastomosis has been formed. The stomach is decompressed with a nasogastric tube and intravenous fluids are given, with oral feeding being introduced as gastric dysmotility resolves.